2019
DOI: 10.3889/oamjms.2019.093
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Intralesional Triamcilonon Acetonide Injection in Keloid Patients

Abstract: AIM:Evaluation the effect of intralesional corticosteroid injection on keloid, at the National Hospital of Dermatology and Venereology from 1/2009 to 12/2009.METHODS:A group of 65 patients with keloid were randomly assigned into three groups. In the studied group, 33 patients were intralesionally injected 7.5 mg/1 cm2 of TCA. In the control group, TAC 32 patients were intralesionally injected 15 mg/1 cm2 of TCA. The result was evaluated basing on the criteria of Henderson (1998) and El-Tonsy (1996).RESULTS:In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…1 flowchart). Of these included studies, only one study compared the effect of two different doses of TAC directly [10], thirty-four studies investigated different therapies for keloids, with the TAC group being either the treatment or the control arm, and three studies primarily investigated the effect of local anesthetics on injection pain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 flowchart). Of these included studies, only one study compared the effect of two different doses of TAC directly [10], thirty-four studies investigated different therapies for keloids, with the TAC group being either the treatment or the control arm, and three studies primarily investigated the effect of local anesthetics on injection pain.…”
Section: Resultsmentioning
confidence: 99%
“…Belie 2021 [40] Serag-Eldin 2021 [28] Neinaa 2021 [36] Albalat 2021 [44] Ali 2021 [38] Kaushal 2020 [6] Hewedy 2020 [42] Gamil 2020 [41] Manzoor 2020 [24] Huu 2019 [10] Khan 2019 [45] Rasaii 2019 [34] Khalid 2018 [11] Aggarwal 2018 [31] Hietanen 2019 [33] Srivastava 2018 Jan [18] Srivastava 2018 Jun [37] Wang 2018 [7] Chen 2017 [17] Nor 2017 [25] Saleem 2017 [43] Ali 2016 [16] Shaarawy 2015 [30] Payapvipapong 2015 [12] Uzair 2015 [26] Khan 2014 [13] Saha 2012 [35] Sadeghinia 2012 [19] Prabhu 2012 [23] Salem 2009 [29] Anchlia 2009 [20] Koc 2008 [14] Berman 2008 [27] Layton 1994 [39] Usanakornkul 2017 [21] Wang 2017 [15] Jongkajornpong 2021 [22] Taweepraditpol 2020 [32] Domains: D1: Bias arising from the randomization process. D2: Bias due to deviations from intended intervention.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang JQ used ultrasound-guided drug injections to treat scarring and monitored the level of drug injections and the scope of the drug dispersion in real time ( Zhang et al, 2017 ). Other studies have shown that ultrasound can prevent the formation of scar ulcers by injecting the guided drug into the scarred skin in real time ( Dinh Huu et al, 2019 ). In addition, Thompson et al (2015) reported that multiple injections of steroid treatment of distinguishing keloids can be ultrasound-guided to distinguish between injection keloids with mature areas and immature areas.…”
Section: Application In Other Areas Of Medical Cosmetologymentioning
confidence: 99%